Pembelajaran Kewirausahaan di SD Kelas Tinggi Untuk Membentuk Jiwa Entrepreneurship - Iga Ghufrani Juniarti; Nurassyifa Qurotul Aini; Tin Rustini (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Entrepreneurship is currently very developed and is in great demand by the general public. This is because it is stated that there are many opportunities resulting from the entrepreneurial skills they have. Apart from that, the president also directly instructed the urgency of entrepreneurship education in schools. So that entrepreneurship is currently being enhanced through entrepreneurship education at the primary and secondary school levels. Apart from that, entrepreneurship education is also needed within the family and community through fairy tales or stories with the aim of motivating students to become successful as entrepreneurs. Entrepreneurship education focuses a lot on the skills to become an entrepreneur, not just selling goods or services because the basic values of entrepreneurship are important in forming life skills. These skills include creative, innovative, independent, financial management, leadership, courage to take risks, and adaptive. Through this article, entrepreneurship and its scientific fields are discussed at the elementary school level in high school to form students' entrepreneurial spirit. This article also covers the results of other relevant studies which are explained descriptively.